2009
DOI: 10.1007/s00417-009-1144-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and superior ophthalmic vein blood flow velocity in Graves’ orbitopathy: relation with the clinical features

Abstract: IOP and SOV-BFV have significant association with the clinical features of Graves' orbitopathy. The decrease in SOV-BFV increases the severity of Graves' orbitopathy, and may have a role in the clinical course of dysthyroid optic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 18 publications
2
64
1
1
Order By: Relevance
“…Such alterations in normal function of the ocular surface and corneal microstructure have been described previously. 18,19 Similarly, in confocal biomicroscopy of TED patients, Villani and colleagues found a significant reduction in corneal epithelial cell density, increased number of basal epithelial cells, increased stromal cell density, and increased number of activated keratocytes. They suggested that 2 inflammatory mechanisms are responsible for these structural changes: dry eye syndrome and systemic disease itself.…”
Section: Discussionmentioning
confidence: 93%
“…Such alterations in normal function of the ocular surface and corneal microstructure have been described previously. 18,19 Similarly, in confocal biomicroscopy of TED patients, Villani and colleagues found a significant reduction in corneal epithelial cell density, increased number of basal epithelial cells, increased stromal cell density, and increased number of activated keratocytes. They suggested that 2 inflammatory mechanisms are responsible for these structural changes: dry eye syndrome and systemic disease itself.…”
Section: Discussionmentioning
confidence: 93%
“…18 Elevated episcleral venous pressure value has been demonstrated in GO, and raised retrobulbar pressure above normal venous pressure has been reported as a possible cause of reduced orbital venous drainage. 19,20 Konuk et al 21 found that the superior ophthalmic vein blood flow velocity was significantly lower in severe GO cases compared with modere and mild ones. The increase in venous pressure may lead to an elevation with IOP in some patients with GO.…”
Section: Eyementioning
confidence: 99%
“…Из шести глазодвигальных мышц чаще поражаются нижняя, медиальная и верх-няя прямые мышцы [8]. Длительное воспаление при ЭОП в дальнейшем приводит к развитию фиброза ретробульбарной клетчатки и глазодвигательных мышц, что выражается в виде ограничения дви-жения глазных яблок и формирования постоянной диплопии [8].…”
Section: клинические проявления эопunclassified